An ownership transfer protocol for wearable devices - Shun HU; Jian WENG; Jia-nan LIU (网络与信息安全学报)
Recently,wearable devices acted as a kind of smart devices are changing people’s life style.When these devices are used in multi-user setting,ownership transfer should usually be considered.To resolve the security and privacy problems introduced in the ownership transfer process of wearable devices,a secure ownership transfer pro-tocol including initialization,mutual authentication and key change for wearable devices was introduced.The secu-rity analysis indicates that the proposed protocol can resist either normal channel attacks or special attacks appeared in the ownership transfer scenarios.The experiment results indicate that the proposed scheme is fairy efficient and is quite suitable for wearable devices.